6-Thio-substituted-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones with the dialkylaminoethyl moiety – a new class of antivirial agents - Voskoboynik, O. Yu.; Berest, G. G.; Nosulenko, I. S.; Antypenko, L. M.; Krivoschey, O. V.; Shvets, V. M.; Kovalenko, S. I.; Воскобойнік, Олексій Юрійович; Берест, Галина Григорівна; Носуленко, Інна Степанівна; Антипенко, Людмила Миколаївна; Кривошей, Оксана Вікторівна; et al. (НФаУ, 2016)
It has been found that 6-[(l3-dialkylaminoethylthio]-3-R-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones exhibit the antiviral activity against respiratory and the biodefence virus panel (EC50 3.2-36.0 mg/ml) and the influenza type A and B (EC50 1.1-18.0 mg/ml) in the visual (viral CPE) and neutral red dye uptake increasing tests. The high inhibitory activity of compound 1.5 against the strain Flu B (EC50 1.1-5.3 mg/ml) has been revealed. It has been suggested that the antiviral effect of compound 1.5 is comparable with Ribavirin. It has been shown that the planar [1,2,4]triazino[2,3-c]quinazoline system causes antiviral properties additionally determined by the b-dialkylaminoethylthiol fragment and depends on the nature of the substituent in position 3.
6-тіозаміщені 2H-[1,2,4]триазино[2,3-c]хіназолін-2-oни з діалкіламіноетильним фрагментом – новий клас противірусних агентів
Keywords: 6-[β-dialkylaminoethylthio]-3-R-2H-[1,2,4]triazino[2,3-c]quinazolin-2-ones; biodefence viruses; respiratory viruses; antiviral activity